IMPLEMENTASI METODE JARIMATIKA BERBANTUAN MEDIA REPLIKA TERHADAP HASIL BELAJAR SISWA PADA MATERI PERKALIAN BILANGAN CACAH DI MIN 3 BANDA ACEH - Muharni, Syifa Zia; Jarmita, Nida; Zainuddin, Zainuddin (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2026)
The action research in this classroom was undertaken as a result of the fourth-grade students in MIN 3 Banda Aceh struggling to grasp the concepts of multiplication and recalling what they have learned before, which impacted their learning performance. The purpose of the study was to enhance the learning outcome of students in multiplication using Jarimatika method with the help of replica media. It consisted of 40 students and was conducted in three cycles. Teacher and student activities and learning achievement tests were used as data collection methods in the form of observation sheets. The success indicators were teacher and student activity scores ≥80%, individual mastery, at least 75 and classical mastery, >85. The findings indicated improvement throughout the cycles. Teacher activity increased from 69.31% to 78.40% and 90.90%, student activity from 62.61% to 76.90% and 90.47%, and learning outcomes from 67.5% to 77.5% and 90%. Thus, Jarimatika method was found to be effective with the help of replica media, which enhanced the learning outcomes of students in multiplication. Keywords: Jarimatika, Replica Media, Multiplication, Learning Outcomes, Students